THE IMPLEMENTATION OF KAKI READING TECHNIQUES WITH QUANTUM LEARNING STYLE IN READING COMPREHENSIVE LEARNING (PENERAPAN TEKNIK MEMBACA KAKI GAYA QUANTUM LEARNING DALAM PEMBELAJARAN MEMBACA KOMPREHENSIF) - Dian Uswatun Hasanah; Ferdian Achsani; Husnul Septiana (Jurnal Gramatika, 2020)
Reading is an obligation for students, Therefore, Indonesian Tadris students who will become educators should also be able to develop reading skills. Unfortunately, this is still far from expectations, thus it is necessary to apply the right and suitable method to increase student passion in the reading comprehensive subject. The purpose of this study was to describe the implementation, benefits, constraints, and solutions of the KaKi technique with quantum learning style in the Comprehensive Reading learning. This study used descriptive qualitative with a case study research approach. The data sources are obtained from places, events, informants, and documents. Places and events are the processes of implementing learning carried out in the classroom. The informants in this study were Indonesian Tadris Department students. The documents studied are related to the implementation of Comprehensive Reading learning. The data obtained were analyzed using an interactive analysis model which included data reduction, data presentation, and drawing conclusions or verification. The results showed that 1) the implementation of the KaKi technique with Quantum Learning Style was suitable with the  RPS or Semester Learning Plan compiled by lecturers following curriculum standards. 2) There are benefits in implementing the KaKi technique with Quantum Learning Style. 3) There are constraints in implementing the KaKi technique with Quantum Learning Style.